On the physically non‐linear analysis of cyclic loaded reinforced concrete cross‐sections with mathematical optimisation - Raue, Erich; Timmler, Hans-Georg; Garke, Robert (Journal of Civil Engineering and Management, 2009)
In the paper, experimental results of tension member tests are used as a basis from which to develop an extended tension stiffening model for reinforced concrete, with emphasis on the specific concrete damage and the developments of residual deformations depending on the structural loading. Two characteristics are contained in the proposed model: one describes the residual deformation behaviour along the reinforcement accounting for the cracks that cannot be closed completely, while the other describes the degradation of the concrete stiffness. Within context of non‐linear analysis, the model is incorporated into an analytical approach, based on the LAG RANGE principle of minimum of total potential energy. The mechanical problem is solved with the application of the mathematical optimisation, using energy principles formulated as a kinematic formulation and transforming them into non‐linear optimisation problems. It was demonstrated, that this approach is eminently suitable for analysing pre‐damaged or pre‐loaded reinforced concrete cross‐sections under cyclic loading.SantraukaPateikti tempiamųjų gelžbetoninių elementų eksperimentinių tyrimų rezultatai. Remiantis šiais rezultatais pasiūlytas supleišėjusio tempiamojo betono modelis, kuriame įvertinama betono pažaidų ir liekamųjų deformacijų didėjimo įtaka tempiamųjų gelžbetoninių elementų elgsenai. Modelis susideda iš dviejų komponentų: pirmasis aprašo išilginių liekamųjų deformacijų armatūroje kitimą, o antrasis betono įtakos elemento skerspjūvio deformacijoms mažėjimą. Netiesinė analizė atliekama taikant analizinį algoritmą, kuris pagrįstas Lagranžo potencinės energijos minimalumo principu. Mechaninė problema išspręsta taikant matematinį optimizavimą ir energinius principus. Pastarieji aprašyti kinematinėmis formuluotėmis jas perkeliant į netiesinio optimizavimo uždavinio algoritmus. Parodyta, kad pasiūlytas algoritmas gerai tinka cikline apkrova veikiamiems gelžbetoniniams elementams analizuoti.First Published Online: 14 Oct 2010Reikšminiai žodžiai: tempiamų elementų bandymai, betono standumo mažėjimas, liekamosios deformacijos, skerspjūvio analizė, matematinis optimizavimas.